2023
DOI: 10.1093/jsxmed/qdac053
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fractional CO2 laser treatment to the vestibule: a randomized, double-blind, sham-controlled, prospective 3-site clinical study in women with vestibular pain

Abstract: Background Data are limited regarding fractional CO2 laser as a nonhormonal treatment for vestibular pain. Aim We sought to perform what is, to our knowledge, the first multisite prospective randomized, double-blind, sham-controlled clinical trial to assess the safety and efficacy of fractional CO2 laser treatment to the vestibule in women with vestibular pain. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In addition, none of the outcome measures have yet been validated, although they have been used in multiple studies. 21 , 25 , 26 , 28 To the best of our knowledge, there are no established and validated outcome measures to assess vestibular tissue health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, none of the outcome measures have yet been validated, although they have been used in multiple studies. 21 , 25 , 26 , 28 To the best of our knowledge, there are no established and validated outcome measures to assess vestibular tissue health.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual event diary has not been validated but has been previously reported. 26 , 28 Adverse events were collected at every visit.…”
Section: Methodsmentioning
confidence: 99%
“…One randomized controlled trial (RCT) 20,21 and two case series 18,19 of patients undergoing fractional CO2 laser therapy for LPV reported positive outcomes.…”
Section: Co2 Fractional Laser Therapymentioning
confidence: 99%
“…Ninomiya and Sekiguchi 19 administered three treatments at one-month intervals to twenty premenopausal participants using fractional CO2 laser at "basic settings" that could be adjusted at the physician's discretion. The randomized trials reported by Goldstein et al 20,21 examined the effectiveness of CO2 fractional laser therapy (30W) among 70 LPV participants, followed by an open-label treatment of those in the control group. Participants were randomized 2:1 for active treatment and sham, respectively.…”
Section: Co2 Fractional Laser Therapymentioning
confidence: 99%
See 1 more Smart Citation